Enhancing Teacher Competence through Continuous Professional Development: A Case Study at Brawijaya Smart School - Noviyanti, Shobihatul Fitroh; Suti’ah; Mulyadi; Wahananto, Juri; Zikri, Ihsan (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2024)
This study investigates the implementation and impact of the Continuous Professional Development (PKB) program at Brawijaya Smart School (BSS) in Malang, Indonesia. Employing a mixed-methods approach, the research evaluates the program's effects on teacher competence in pedagogical, professional, social, and personal domains. Data collection methods included observations, interviews, and document analysis. Findings suggest that structured development activities significantly enhance teacher competencies. Recommendations include aligning professional development initiatives with teacher needs for continuous improvement.